2014
DOI: 10.9734/arrb/2014/8722
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergy Potentials of Elephant Grass, Pennisetum purpureum Schumach

Abstract: Aim: Wild strains of elephant grass, Pennisetum purpureum, occur as invasive weed especially in disturbed freshwater swamps of Bayelsa State, Nigeria. A study was undertaken to assess the productivity and bioenergy potentials of the grass. Study Design: A completely randomized experimental design was used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 62 publications
0
7
1
Order By: Relevance
“…The mean DM yield of the present result 14.13 t/ha was higher than the previous finding of 12.77 t/ha at 2 months age as reported by [10] and lower than the other findings of which was 41.05 t/ha at 4 months age as reported by [44] which might be due to the proportional increment of dry matter yield with advance in age of cutting [32]. [45] findings also showed that the dry matter yield of the wild Napier grass at first cut (harvest) ranged from 7.00-11.33 t/ha and [46] reported that yields depend on agro-ecological zone and management but on average Napier grass can give 12 to 25 t/ha of dry matter yield.…”
Section: Agronomic Traits Of Napier Grass Cultivarscontrasting
confidence: 87%
See 1 more Smart Citation
“…The mean DM yield of the present result 14.13 t/ha was higher than the previous finding of 12.77 t/ha at 2 months age as reported by [10] and lower than the other findings of which was 41.05 t/ha at 4 months age as reported by [44] which might be due to the proportional increment of dry matter yield with advance in age of cutting [32]. [45] findings also showed that the dry matter yield of the wild Napier grass at first cut (harvest) ranged from 7.00-11.33 t/ha and [46] reported that yields depend on agro-ecological zone and management but on average Napier grass can give 12 to 25 t/ha of dry matter yield.…”
Section: Agronomic Traits Of Napier Grass Cultivarscontrasting
confidence: 87%
“…The result obtained from present findings was less than the fresh biomass obtained during adaptation trial at Mechara Agricultural Research Center on a station that was 163.17t/ha from ILRI#16800 and 157.3 t/ha ILRI#16840 at the age of 8 months [43]. [45] reported that similar result that wet weight of Napier grass ranged from 55.67±4.67 to 86.67±6.39 t/ha) and [17] reported 18.6 kg/m 2 which is equal to 186 t/ha. Means followed by different superscript letters within a column are significantly different each other at P < 0.05.…”
Section: Agronomic Traits Of Napier Grass Cultivarsmentioning
confidence: 78%
“…It was introduced as forage in many tropical and subtropical regions of the world because of its ability to produce high biomass yield under a wide range of climatic and edaphic conditions (Aroeira et al, 2001) Elephantgrass is highly efficient in fixing atmospheric CO 2 and able to accumulate more than 60 Mg ha -1 of dry matter per year (Morais et al, 2009). Although elephant grass is mainly used as an animal feed (Santos et al, 2013;Rusdy, 2016), the high biomass production, especially in tropical countries, makes it a potential feedstock for bioenergy production (Flores et al, 2012;Ohimain;Kendabie;Nwachukwu, 2014;Sales et al, 2015). As a result, research has been directed to using elephant grass biomass for biofuel production such as charcoal (Strezov;Evans;Hayman, 2008), alcohol (Soares et al, 2011), methane, or even for direct burning (Samson et al, 2005;Lee et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…is suitable for this purpose and widely used in cattle raising, mainly for cutting, grazing and silage production (Santos et al, 2013;Maia et al, 2015). In addition to being an excellent animal feed, elephant grass can also be used as raw material for the production of bio-gas, bio-oil, charcoal (Strezov et al, 2008;Rocha et al, 2017), and alcohol (Shakil et al, 2013), as well as for the generation of electricity (Ohimain et al, 2014).…”
Section: Introductionmentioning
confidence: 99%